Draft Whole-Genome Sequences of Escherichia fergusonii Strains Isolated from Beef Trim (GTA-EF02), Ground Beef (GTA-EF03), and Chopped Kale (GTA-EF04) - Manninger, Paul (Genome Announc, 2016)
Escherichia fergusonii is a Gram-negative, rod-shaped, non-spore-forming member of the Enterobacteriaceae family and is a bacterium with both biotechnological applications and implication in human clinical disease. Here, we report the draft genome sequences of three isolates of E. fergusonii from beef trim (GTA-EF02), ground beef (GTA-EF03), and chopped kale (GTA-EF04).